Território kínēma: uma trilha da caverna à nuvem - Soares Neto, Francisco (2015)
This research starts from the image culture perspective questioning if a look at the historical and evolutionary trajectory of immersion illusion devices that are grounded in spaces, technologies and body, reveals elements concerning the territory of communication studies on cinema culture in its scope, which appropriates these elements; or would constitute another phenomenon, another artistic language that incorporates the term "cinema", which etymologically suggests movement. The hypothesis is that the surveyed equations would point to results of experiential aesthetic experiences, personal and collective, in which the subject, once the viewer, would become an active element, observer and absorber of a cinema "expanded". Meet and present relations in the subject's confrontation with the environment and with the technologies would enable a better understanding of the process of transit between immersion and emersion, now expanding the space and time, with the possibility of extended life, omnipotence and omnipresence, sometimes providing an experience of a biological impersonal reductionism . To obtain a satisfactory reflection on the subject in question, historically sought to research a corpus composed of audiovisual works of relevance, from pre-cinema to contemporary era. Through research in books, journals and Internet sites are listed historical data, technical data, evolution and appropriation of space, technology, and experiments, as well as future possibilities of cinematographic workmanship. Some fictional movies that thematize the technological vision are discussed as possible references of experiential expansion in factual reality, also to reveal other possible spaces Kinematica projection, as in the case of Tron, which deals with virtual reality. Authors such as Gene Youngblood, Jean Baudrillard, André Parente, Arlindo Machado, Ismail Xavier, Lucia Santaella, among others, are the theoretical contributors that dialogue with the suggested and implied questions in defining the issue.